Respuesta :

if you need to solve this problem through substitution, then we need to change the first equation because we need one of the equations to be y= or x=.

-x+y=4
+x     +x
y=4+x

ok, so substitute the above equation into the y-value of the second equation.

2x-3(4+x) = -5
2x-12-3x = -5
-x-12 = -5
   +12   +12
-x = 7
/-1   /-1

x = -7

Now, substitute the x-value into one of the equations from the given.

-x+y=4
-(-7)+y=4
7+y=4
-7     -7
y = -3

So, the answer is (-7,-3)

HOPE THIS HELPS!!!